E-marketing implementation in small and medium-sized restaurants in Palestine - Abeer Qashou; Yahya Saleh (Arab Economic and Business Journal, 2018)
This study investigates the factors affecting the acceptance and implementation of E-marketing and its impact on marketing performance in small and medium-sized restaurants (SMRs) in Palestine. Potential factors were derived and conceptually-modelled for analysis based on popular technology acceptance models in literature. Three contexts (technological, organizational and environmental) with sixteen factors were hypothesized to influence E-marketing in the SMRs. Relevant data were gathered from a randomly-selected sample of 223 SMRs working in Palestine. Data were reported by participants using a self-report questionnaire. Pearson correlation and multiple linear regression were employed to analyze the collected data. The results revealed that all individual hypothesized factors have positive significant impact on E-marketing implementation. Regression models indicated that relative advantage, customer pressure and market scope have significant positive impact on implementation. The regression analysis also shows that E-marketing has a positive significant impact on marketing performance. The implications of this study which would benefit all stakeholders within the SMRs context are highlighted.
Keywords: 650; E-marketing; Small and medium-sized restaurants; Technology Acceptance Model (TAM); Innovation Diffusion Theory (IDT); Technology-Organization Environment (TOE); Marketing performance